2010
DOI: 10.1177/0961203309360809
|View full text |Cite
|
Sign up to set email alerts
|

Use of monoclonal antibodies to dissect specificity and pathogenesis of antiphospholipid antibodies

Abstract: Monoclonal antiphospholipid antibodies (aPL) have been utilized to dissect the relationship between their sequence, structure, binding and biological properties relevant to the pathogenesis of the antiphospholipid syndrome. In particular, sequence analysis of aPL has highlighted the clustering of certain amino acid residues in the antigen contact sites of their heavy and light chains. Therefore, these sequence motifs are likely to be important in determining aPL binding properties and their pathogenic effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Genes such as TLR4, Annexin II, VEGF, TGFβ, C3R, PKC, PKN, BCL2 as well as many genes involved in mitochondrial function and oxidative stress like MPO, GPX3, DUOX1, UCP3 were common to both our results and the previous studies of Lopez-Pedrera's group [8,12]. In addition, we confirmed our previous findings comparing the intracellular effects of VT+/PM- and VT-/PM+ IgG in monocytes [7]. This microarray analysis found the regulation of MAPKK kinase signalling and cell communication through Ikappa kinase/NF-kappa-B cascade to be a distinctive feature of VT+/PM- IgG.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Genes such as TLR4, Annexin II, VEGF, TGFβ, C3R, PKC, PKN, BCL2 as well as many genes involved in mitochondrial function and oxidative stress like MPO, GPX3, DUOX1, UCP3 were common to both our results and the previous studies of Lopez-Pedrera's group [8,12]. In addition, we confirmed our previous findings comparing the intracellular effects of VT+/PM- and VT-/PM+ IgG in monocytes [7]. This microarray analysis found the regulation of MAPKK kinase signalling and cell communication through Ikappa kinase/NF-kappa-B cascade to be a distinctive feature of VT+/PM- IgG.…”
Section: Discussionsupporting
confidence: 91%
“…A few studies found differences in the effects of aPL from patients with and without thrombosis upon various signalling pathways in target cells [[4], [5], [6], [7]]. Proteomic analyses of monocytes isolated from patients with APS [8] and healthy monocytes treated with APS-IgG [9] have shown that the monocyte proteome is differentially regulated by IgG from obstetric compared to thrombotic APS.…”
Section: Introductionmentioning
confidence: 99%